Specific Localization of an Auto-inhibition Mechanism at Presynaptic Terminals of Identified Serotonergic Neurons. (15th March 2021) - García-Ávila, Miriam; Torres, Ximena; Cercós, Montserrat G.; Trueta, Citlali
Graphical abstract: Highlights: A Cl − -dependent auto-inhibition mechanism is only localized at presynaptic terminals. The auto-inhibition mechanism is not present at the soma or primary axon. Peri-synaptic release from dense-core vesicles contributes to auto-inhibition. Abstract: Auto-regulation mechanisms in serotonergic neurons regulate their electrical activity and secretion. Since these neurons release serotonin from different structural compartments – including presynaptic terminals, soma, axons and dendrites – through different mechanisms, autoregulation mechanisms are also likely to be different at each compartment. Here we show that a chloride-mediated auto-inhibitory mechanism is exclusively localized at presynaptic terminals, but not at extrasynaptic release sites, in serotonergic Retzius neurons of the leech. An auto-inhibition response was observed immediately after intracellular stimulation with an electrode placed in the soma, in neurons that were isolated and cultured retaining an axonal stump, where presynaptic terminals are formed near the soma, but not in somata isolated without axon, where no synaptic terminals are formed, nor in neurons in the nerve ganglion, where terminals are electrotonically distant from the soma. Furthermore, no auto-inhibition response was detected in either condition during the longer time course of somatic secretion. This shows that the auto-inhibition effects are unique to nerve terminals. We further determined that serotonin released from peri-synaptic dense-core vesicles contributes to auto-inhibition in the terminals, since blockade of L-type calcium channels, which are required to stimulate extrasynaptic but not synaptic release, decreased the amplitude of the auto-inhibition response. Our results show that the auto-regulation mechanism at presynaptic terminals is unique and different from that described in the soma of these neurons, further highlighting the differences in the mechanisms regulating serotonin release from different neuronal compartments, which expand the possibilities of a single neuron to perform multiple functions in the nervous system.